2015
DOI: 10.1371/journal.pone.0131595
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium Glutamate Dietary Consumption Decreases Pancreatic β-Cell Mass in Adult Wistar Rats

Abstract: BackgroundThe amount of dietary monosodium glutamate (MSG) is increasing worldwide, in parallel with the epidemics of metabolic syndrome. Parenteral administration of MSG to rodents induces obesity, hyperglycemia, hyperlipidemia, insulin resistance, and type 2 diabetes. However, the impact of dietary MSG is still being debated. We investigated the morphological and functional effects of prolonged MSG consumption on rat glucose metabolism and on pancreatic islet histology.MethodsEighty adult male Wistar rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 44 publications
(60 reference statements)
5
28
0
2
Order By: Relevance
“…These results suggested that brief exposure to glutamate stimulated insulin secretion from β-cells. However, Boonnate has reported that daily consumption of dietary glutamate decreased the pancreatic β-cell mass in adult rats34. The present data showed that chronic high-glucose treatment doubled the glutamate content in culture media of RINm5f cells, indicating that endogenous glutamate may be released from β-cells under chronic hyperglycemic conditions.…”
Section: Discussionsupporting
confidence: 43%
“…These results suggested that brief exposure to glutamate stimulated insulin secretion from β-cells. However, Boonnate has reported that daily consumption of dietary glutamate decreased the pancreatic β-cell mass in adult rats34. The present data showed that chronic high-glucose treatment doubled the glutamate content in culture media of RINm5f cells, indicating that endogenous glutamate may be released from β-cells under chronic hyperglycemic conditions.…”
Section: Discussionsupporting
confidence: 43%
“…In fact, monosodium glutamate (MSG), a substance used to produce an animal model of obesity , was shown to annul the effects of GLP‐1 by destroying the ARC after subcutaneous injection in rodents . More recently, rats treated with MSG (2 mg g −1 body weight in drinking water, daily) showed a reduced pancreatic β ‐cell mass, accompanied by hemorrhagic and fibrotic lesions, although glucose homeostasis remained unaffected; this suggests that in the presence or susceptibility to diabetes or sodium chloride, the pancreas might functionally manifest the dietary MSG negative effect .…”
Section: Incretins In Obesitymentioning
confidence: 99%
“…In this vein, culminating data point out a significant association between dietary MSG and increased abdominal or retroperitoneal body fat content either in the presence or absence of total body weight gain compared with control high caloric chow-fed rats (Collison et al, 2010;Afifi and Abbas, 2011;Khalaf and Arafat, 2015). The coexistence of adipocyte hypertrophy and the reduced proliferative capacity of APCs (hyperplasia) in MSGobese animals is consistent with the abnormal expansion of fat tissue in obesity, wherein the pathologically relevant adipocyte hypertrophy gain dominance over the hyperplasia in adapting to chronic energy surplus (Takasaki, 1978;Terry et al, 1981;Fernstrom et al, 1996;Kondoh et al, 2005;Ortiz et al, 2006;Collison et al, 2009;Boonnate et al, 2015;Huang et al, 2017). Adipocyte hypertrophy and associated inflammation in adipose tissue is the hallmark of obesity pathogenesis in both human subjects and animal models (Hill and Peters, 1998;He et al, 2008;Shi et al, 2010;Insawang et al, 2012;Thu Hien et al, 2013).…”
Section: Introductionmentioning
confidence: 81%